Impact of the pretransplant dialysis modality on kidney transplantation outcomes: a nationwide cohort study. Issue 6 (4th June 2018) - Lin, Huan-Tang; Liu, Fu-Chao; Lin, Jr-Rung; Pang, See-Tong; Yu, Huang-Ping
Abstract : Objective: Most patients with uraemia must undergo chronic dialysis while awaiting kidney transplantation; however, the role of the pretransplant dialysis modality on the outcomes of kidney transplantation remains obscure. The objective of this study was to clarify the associations between the pretransplant dialysis modality, namely haemodialysis (HD) or peritoneal dialysis (PD), and the development of post-transplant de novo diseases, allograft failure and all-cause mortality for kidney-transplant recipients. Design: Retrospective nationwide cohort study. Setting: Data retrieved from the Taiwan National Health Insurance Research Database. Participants: The National Health Insurance database was explored for patients who received kidney transplantation in Taiwan during 1998–2011 and underwent dialysis >90 days before transplantation. Outcome measures: The pretransplant characteristics, complications during kidney transplantation and post-transplant outcomes were statistically analysed and compared between the HD and PD groups. Cox regression analysis was used to evaluate the HR of the dialysis modality on graft failure and all-cause mortality. The primary outcomes were long-term post-transplant death-censored allograft failure and all-cause mortality started after 90 days of kidney transplantation until the end of follow-up. The secondary outcomes were events during kidney transplantation and post-transplant de novo diseases adjusted by propensity score in log-binomial model. Results: There were 1812 patients included in our cohort, among which 1209 (66.7%) and 603 (33.3%) recipients received pretransplant HD and PD, respectively. Recipients with chronic HD were generally older and male, had higher risks of developing post-transplant de novo ischaemic heart disease, tuberculosis and hepatitis C after adjustment. Pretransplant HD contributed to higher graft failure in the multivariate analysis (HR 1.38, p<0.05) after adjustment for the recipient age, sex, duration of dialysis and pretransplant diseases. There was no significant between-group difference in overall survival. Conclusions: Pretransplant HD contributed to higher risks of death-censored allograft failure after kidney transplantation when compared with PD.